Immunoelectron Microscopy of Schffier's Dots in Plasmodium vivax -Infected Human Erythrocytes - Udagama, Preethi V; Atkinson, Carter T; Peiris, J. S.M.; David, Peter H; Mendis, Kamini N; Aikawa, Masamtchi (American Journal of Pathology, 1988)
Plasmodium vivax induces morphologic alterations in infected host erythrocytes that are visible by light microscopy in Romanovsky-stained blood smears as multiple brick-red dots. These morphologic changes, referred to as Schiiffner's dots, are important in the identification of this species of malarial parasite and have been associated by electron microscopy with caveolavesicle complexes along the erythrocyte plasma-lemma. We have produced a monoclonal antibody (MAb A 20) that identifies an antigen in Plasmodium vivax-infected erythrocytes that is associated with the caveola-vesicle complexes of the parasitized host cell. This monoclonal antibody reacts with air-dried P. vivax-infected erythrocytes to produce a pattern by the indirect immunofluorescence test (IFT)-that is evocative of Schiiffner's dots. Immunoelectron microscopy of P vivax infected human erythrocytes using MAb'A 20 confirmed the location of this antigen within vesicles of caveola-vesicle complexes. On Western blots, MAb A 20 recognized four polypeptides of 54, 64,12, and 86 kd. MAb A 20 reacted 6y IFf with 900/o of Sri Lankan isolates and with a Brazilian P vivax isolate, which indicates that the epitope identified by this monoclonal is conserved. (A- J pathol 19gg; 131: 48-s2)
Keywords: Immunoelectron; Plasmodium vivax; Microscope; Erythrocytes; Human